Konstruksi Media Online Mengenai Pemberitaan Blame Game Terkait Asal Mula Virus Corona Muncul - Muhammad Yudistira Meydianto (Syntax Idea, 2020)
The purpose of this research is to see how the news packaging of the two media is opposite each other. Research Methods Text analysis with the analysis of the Robert N. Entman version of the framing approach. The subjects of this research are the New York Times and Xinhua.com media, while the object of this research is the news released from the two media relating to mutual accusations of the origin of the corona virus appearing. The theory of framing analysis uses the concept of Robert N. Entman. According to Entman, framing is viewed on 2 major dimensions, namely: “Selection of gossip and highlighting aspects. Prominence is the process of making facts more interesting, more interesting, meaningful or more memorable to the audience. The reality that is presented in a prominent way has a greater possibility to be noticed and to hypnotize the audience about a reality. The Chinese side's research results rejected Trump's accusation that the corona virus was deliberately created and originated from China, Trump also could not provide valid evidence so that China emphasized more that they rejected the accusation, while the New York Times supported Trump's statement. But on the other hand, the New York Times also blamed Trump for the corona virus in the United States because of his slow handling.